Investigation on mechanical properties of dissimilar metals using MIG welding. (2021) - Sakthivel, P.; Manobbala, V.; Manikandan, T.; Mohammed Arman Salik, Z.; Rajkamal, G.
Abstract: In this experiment, using the Metal Inert Gas welding process we will investigate the mechanical properties of aluminum alloys (AA6063, AA7075, AA2014), and mild steel. MIG is favored since the welding process provides clean welding with better quality and also with reduced slag in the weld. The use of MIG welding to combine dissimilar materials is a new area for weight reduction in power generation, electrical, nuclear, petrochemical, and chemical industries. Because of the thermal, mechanical and chemical properties of the materials, a number of problems will be faced in welding these dissimilar metals through the whole process such as cracking, reduction of strength, porosity, surface quality and stress. Like Mild Iron, aluminum alloys have lower density and better mechanical properties. Because of its lightweight properties these aluminum alloys are used in the aerospace and automotive industries. Dissimilar metal alloys of aluminum 6063, 7075, and 2014 were butt jointed with mild steel respectively using a MIG welding process. The mechanical properties of dissimilar materials were tested by performing the tensile test, the Rockwell Hardness test, the Vickers hardness test, the macro and micro test showing an overall weld quality and a good appearance on the welded region as micro and macrostructure are used to examine the quality and weld zone. Finally, we conclude that from the results of Tensile, Rockwell and Vickers hardness the weldability and strength quality is good in AA6063.